The risk and nature of flares in juvenile idiopathic arthritis: results from the ReACCh-Out cohort. Issue 6 (18th May 2015) - Guzman, Jaime; Oen, Kiem; Huber, Adam M; Watanabe Duffy, Karen; Boire, Gilles; Shiff, Natalie; Berard, Roberta A; Levy, Deborah M; Stringer, Elizabeth; Scuccimarri, Rosie; Morishita, Kimberly; Johnson, Nicole; et al.
Abstract : Objective: To describe probabilities and characteristics of disease flares in children with juvenile idiopathic arthritis (JIA) and to identify clinical features associated with an increased risk of flare. Methods: We studied children in the Research in Arthritis in Canadian Children emphasizing Outcomes (ReACCh-Out) prospective inception cohort. A flare was defined as a recurrence of disease manifestations after attaining inactive disease and was called significant if it required intensification of treatment. Probability of first flare was calculated with Kaplan–Meier methods, and associated features were identified using Cox regression. Results: 1146 children were followed up a median of 24 months after attaining inactive disease. We observed 627 first flares (54.7% of patients) with median active joint count of 1, physician global assessment (PGA) of 12 mm and duration of 27 weeks. Within a year after attaining inactive disease, the probability of flare was 42.5% (95% CI 39% to 46%) for any flare and 26.6% (24% to 30%) for a significant flare. Within a year after stopping treatment, it was 31.7% (28% to 36%) and 25.0% (21% to 29%), respectively. A maximum PGA >30 mm, maximum active joint count >4, rheumatoid factor (RF)-positive polyarthritis, antinuclear antibodies (ANA) and receiving disease-modifying antirheumatic drugs (DMARDs) or biological agents before attaining inactive disease were associated with increased risk of flare. Systemic JIA was associated with the lowest risk of flare. Conclusions: In this real-practice JIA cohort, flares were frequent, usually involved a few swollen joints for an average of 6 months and 60% led to treatment intensification. Children with a severe disease course had an increased risk of flare.